The Electrochemical Oxidation and Mass Transfer Mechanism of Formic Acid on the Catalyst Electrode Surface - Hu, Jie; Wang, Panpan; Chen, Changguo (Frontiers in Chemistry, 2022)
The organic small molecule fuel battery has attracted wild attention in recent years. Unfortunately, the inherent catalyst poisoning phenomenon hinders its commercialization. Exploring the anodic catalytic reaction mechanism is urgent. This article investigates the nucleation mechanism of HCOOH on the catalyst electrode surface. The electrochemical results indicate that the HCOOH oxidation conforms to the two-dimensional instantaneous nucleation process. The corresponding adsorption model of CO on the catalyst surface was finally established.